EFEKTIVITAS METODE PROBLEM-BASED LEARNING PADA MATA KULIAH PSIKOLOGI KEPRIBADIAN I (REPLIKASI) - Titik Kristiyani (LPMPP Universitas Negeri Yogyakarta, 2008)
AbstractThis study aims to investigate (1) whether the problem-based learning (PBL)method is effective to teach a theoretical subject, namely Personality Psychology I,and (2) how effective the PBL is in comparison with the traditional one. This studywas a quasi-experimental study in which two Personality Psychology I classes(Classes A and C) employed the PBL method in the learning process, and the otherclass (Class B) employed the traditional method. The effectiveness was measuredby the outcome-oriented assessment through an achievement test and the processorientedassessment through a learning satisfaction scale and the amount of worktime in groups. The hypothesis was tested by the independent sample t-test. Thestudy shows the following results. (1) There is no significant difference in the scoreof the achievement test between the students in the PBL class and those in thetraditional class. (2) In the process-oriented assessment, there are significantdifferences between the students in the PBL class and those in the traditional class,especially in the learning pleasure, learning difficulties, learning anxiety,perception of the subject matter mastery, and perception of fairness.Keywords: problem-based learning (PBL), traditional learning, outcome-orientedassessment, process-oriented assessment